Developing of Instructional Video Media to Improve Learning Quality and Student Motivation - Sulihin Sulihin; Asbar Asbar; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
This study is about knowing the improvement of student learning outcomes through videos at Muhammadjyah Enrekang University. The problems of this research are: 1) how is the process of application to lessons via video in the PGSD class at Muhammadiyah Enrekang University? 2) Does the application of video lessons through thematic learning can improve student learning outcomes at the University of Muhammadiyah Enrekang? reflect deeply on several aspects of teaching and learning activities. The focus of this research is to improve student learning outcomes through video through thematic learning about natural resources and local economic activities by applying a system of instructional video approaches. The subjects of the study were 125 PGSD students in Enrekang District, consisting of 70 boys and 55 girls. The instruments that have been used are observation, tests and documentation. Data that has been processed with percentage analysis and presented in the form of descriptions and presentations. The findings of its application are asking questions, thinking together and answering; the application of video lessons through learning to improve student learning outcomes reaches 85%. The goals and objectives of education held in schools are formal channels and informal channels.